Antinociceptive effects of sinomenine in a rat model of postoperative pain. (31st March 2016) - Zhu, Qing; Sun, Yuehua; Mao, Lina; Liu, Chengpeng; Jiang, Bo; Zhang, Wei; Li, Jun‐Xu
Abstract : Background and Purpose: This study examined the antinociceptive effects of sinomenine in a rat model of postoperative pain. Experimental Approach: Male and female rats were subjected to a surgical incision in the right hind paw, and the von Frey filament test was used to measure mechanical hypersensitivity after drug or vehicle treatment (p.o. or i.p.). Rats were treated daily with sinomenine before or after the surgery and the AUCs of the antinociceptive effects measured during a 4 h period were calculated to determine the ED50 values of sinomenine. The anti‐hyperalgesic effects of different doses of a combination of sinomenine and acetaminophen (paracetamol) were assessed in another group of rats. Dose combinations were determined by using a fixed ratio dose‐addition analysis method. Key Results: Sinomenine (5–80 mg·kg −1 ) produced dose‐dependent antinociceptive effects in rats that had been subjected to surgery and this effect lasted for 4 h. The potency of sinomenine, given i.p. or p.o., did not differ between male and female rats. However, sinomenine was fourfold more potent when given i.p. than p.o. The GABAA receptor antagonist bicuculline blocked the antinociceptive effects of sinomenine. The antinociceptive effect of a daily treatment with sinomenine remained stable throughout the course of postoperative pain. Pretreatment with sinomenine did not alter the mechanical hypersensitivity post‐surgery. The combination of sinomenine with acetaminophen produced an infra‐additive interaction. Conclusions and Implications: Sinomenine demonstrated significant antinociceptive activity against postoperative pain and may be a useful novel pharmacotherapy for the management of postoperative pain.